Literature Review : The Relationship Between Mothers' Knowledge, Motivation, and the Role of Cadres with Toddler Visits to Integrated Health Posts - Astuti, Indry; Periyanti, Meti; Novitasari; Khairani, Dina; Armiati, Harni; Sofiyanti, Ida (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Posyandu serves as a basic service center to prevent stunting, provide immunizations, monitor weight, and deliver nutrition education for mothers, in order to reduce infant mortality rates. This literature review aims to describe the relationship between maternal knowledge, motivation, and the role of cadres with toddler visits to posyandu. This literature review uses a literature review method. A systematic search was conducted through computer-based searches using the Google Scholar database with articles published between 2021 and 2025. Only articles with quantitative designs and full text were included in this analysis. Key data searches used the PICO technique (Population, Intervention, Compare, Outcome). Of the 15 articles identified, 10 articles were relevant to the topic of this literature review. These 10 articles show that mothers with good knowledge better understand the benefits of posyandu and are therefore more active in bringing their children. Motivation also influences toddler visits. Mothers with high motivation tend to be more consistent in participating in posyandu activities. In addition, the role of cadres has been shown to have a strong relationship with toddler visits. Cadres who are active in providing counseling and encouraging the community can increase the participation of mothers with toddlers. Maternal knowledge, motivation, and the role of cadres are interrelated factors that contribute significantly to increasing visits to posyandu.